2019
DOI: 10.3390/pharmaceutics11110581
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Delta Inulin Conjugates for Controlled and Targeted Drug Delivery: Development, Characterization, and In Vitro Evaluation

Abstract: Delta inulin, also known as microparticulate inulin (MPI), was modified by covalently attaching doxorubicin to its nanostructured surface for use as a targeted drug delivery vehicle. MPI is readily endocytosed by monocytes, macrophages, and dendritic cells and in this study, we sought to utilize this property to develop a system to target anti-cancer drugs to lymphoid organs. We investigated, therefore, whether MPI could be used as a vehicle to deliver doxorubicin selectively, thereby reducing the toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In the case of preparation of APA-ALS-NC, incubation time is similar to reaction time offered for the attachment of ALS (drug) to APA. Increasing reaction time increases the conjugation process, i.e., the attachment of drug [ 36 ]. Thus, increasing incubation time increases the chance for attachment of more drug molecules and subsequent increase in particle size.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of preparation of APA-ALS-NC, incubation time is similar to reaction time offered for the attachment of ALS (drug) to APA. Increasing reaction time increases the conjugation process, i.e., the attachment of drug [ 36 ]. Thus, increasing incubation time increases the chance for attachment of more drug molecules and subsequent increase in particle size.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that both DOX and curcumin suffer from poor bioavailability. In light of this, a wide variety of nanoplatforms have been developed for codelivery of curcumin and DOX [ 179 , 180 , 181 ]. In addition to promoting cellular internalization of DOX, nanocarriers can prevent development of chemoresistance, since a low amount of DOX is loaded on/in the encapsulants.…”
Section: Codelivery Via Biological Nanovehiclesmentioning
confidence: 99%
“…It was observed that the administered delta inulin particles were transported to the liver as well as secondary lymphoid tissue after being primarily taken up by macrophages, hydrolyzed to be dispersed into the bloodstream and finally eliminated into the urine. Furthermore, delta inulin was modified by coating doxorubicin on its nanostructured surface for application in targeted drug delivery for anticancer therapy ( Wang et al, 2019 ). The authors used the property of delta inulin in which it is endocytosed by monocytes to design a platform to transport doxorubicin to lymphoid organs.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 99%
“…In addition, HMI such as amine derivatives have been grafted with biotin, retinoic acid, and vitamin E to produce mucoadhesive micelles, which exhibit transcorneal permeation properties, as well as long-circulating carriers for receptor-mediated targeted drug delivery ( Di Prima et al, 2017 ; Mandracchia et al, 2018 ). Studies have revealed that inulin serves as a promising transporter for colonic drug delivery because it is not digested in the stomach and small intestine ( Wang et al, 2019 ). SCFAs play an important physiological role in combating colon-related diseases and altering gut microbiota compositions.…”
Section: Introductionmentioning
confidence: 99%